2020
DOI: 10.1088/1757-899x/671/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Reducing Energy Consumption for a Building using Geothermal Water through the Glass

Abstract: Electricity consumption is the main criterion for identifying green buildings that contribute to the sustainable development of the world. The aim of this study was to reduce the utilization of electrical energy by air-conditioning devices, by decreasing heat gain via the glass of buildings. The study found that the maximum energy consumption for air conditioners was 48% of total energy in a building. The glass significantly contributes to waste and electrical energy heat loss by heat transfer to the inside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The reduction in cooling load due to the replacement of glass type has also been reported by several experts, including Venkiteswaran et al [2], Albab & Adi [4] and Shaik et al [22], namely 9.5%, 6.2% and 18.9%, respectively. This material replacement is also more effective when compared to the method of flowing water between the glass layers, as reported by Imran et al [21], which was only able to reduce 6%. Research by Shen & Li [20] using double-glazing windows with cooling pipes embedded in venetian blinds reported a 13% reduction in solar energy transmitted into the building.…”
Section: Floormentioning
confidence: 51%
See 1 more Smart Citation
“…The reduction in cooling load due to the replacement of glass type has also been reported by several experts, including Venkiteswaran et al [2], Albab & Adi [4] and Shaik et al [22], namely 9.5%, 6.2% and 18.9%, respectively. This material replacement is also more effective when compared to the method of flowing water between the glass layers, as reported by Imran et al [21], which was only able to reduce 6%. Research by Shen & Li [20] using double-glazing windows with cooling pipes embedded in venetian blinds reported a 13% reduction in solar energy transmitted into the building.…”
Section: Floormentioning
confidence: 51%
“…Shen & Li [20] conducted research using double glazing window embedded pipes, they reported that the developed method can absorb solar radiation up to 60%. Furthermore, Imran et al [21] reported that the use of triple glass filled with water can reduce the cooling capacity by 44.73 TR, while the use of 6 mm clear single glass can only reduce the cooling capacity by 2.3 TR. Using different types of glass in window glazing, Shaik et al [22] reported that the use of polymer dispersed liquid crystal glazing on window glass can reduce the cooling load by 18.9% compared to windows using clear glass.…”
Section: Introductionmentioning
confidence: 99%
“…Air conditioning systems are the major energy consumers in office building, hotel, central library, hospital, shopping mall, residential and others building. Many literatures reported that in commercial building, air conditioning systems account almost half of the total power consumption, and being the single biggest consumers [1][2][3][4][5][6]. It is also found that another building consumes more than 50%-70% for HVAC (Heating, Ventilating, and Air Conditioning) of total electrical energy use [7][8][9].…”
Section: Introductionmentioning
confidence: 99%